Application of Mass Spectrometry in Pancreatic Cancer Translational Research - Ge, Peng; Luo, Yalan; Chen, Haiyang; Liu, Jiayue; Guo, Haoya; Xu, Caiming; Qu, Jialin; Zhang, Guixin; Chen, Hailong (Frontiers in Oncology, 2021)
Pancreatic cancer (PC) is one of the most common malignant tumors in the digestive tract worldwide, with increased morbidity and mortality. In recent years, with the development of surgery, chemotherapy, radiotherapy, targeted therapy, and immunotherapy, and the change of the medical thinking model, remarkable progress has been made in researching comprehensive diagnosis and treatment of PC. However, the present situation of diagnostic and treatment of PC is still unsatisfactory. There is an urgent need for academia to fully integrate the basic research and clinical data from PC to form a research model conducive to clinical translation and promote the proper treatment of PC. This paper summarized the translation progress of mass spectrometry (MS) in the pathogenesis, diagnosis, prognosis, and PC treatment to promote the basic research results of PC into clinical diagnosis and treatment.